Spiral Ganglion Neuron Projection Development to the Hindbrain in Mice Lacking Peripheral and/or Central Target Differentiation - Elliott, Karen L.; Kersigo, Jennifer; Pan, Ning; Jahan, Israt; Fritzsch, Bernd (Frontiers in Neural Circuits, 2017)
We investigate the importance of the degree of peripheral or central target differentiation for mouse auditory afferent navigation to the organ of Corti and auditory nuclei in three different mouse models: first, a mouse in which the differentiation of hair cells, but not central auditory nuclei neurons is compromised (Atoh1-cre; Atoh1f/f); second, a mouse in which hair cell defects are combined with a delayed defect in central auditory nuclei neurons (Pax2-cre; Atoh1f/f), and third, a mouse in which both hair cells and central auditory nuclei are absent (Atoh1-/-). Our results show that neither differentiated peripheral nor the central target cells of inner ear afferents are needed (hair cells, cochlear nucleus neurons) for segregation of vestibular and cochlear afferents within the hindbrain and some degree of base to apex segregation of cochlear afferents. These data suggest that inner ear spiral ganglion neuron processes may predominantly rely on temporally and spatially distinct molecular cues in the region of the targets rather than interaction with differentiated target cells for a crude topological organization. These developmental data imply that auditory neuron navigation properties may have evolved before auditory nuclei.